2021
DOI: 10.3390/en14102857
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer by Natural Convection in a Square Enclosure Containing PCM Suspensions

Abstract: Research on using phase change material (PCM) suspension to improve the heat transfer and energy storage capabilities of thermal systems is booming; however, there are limited studies on the application of PCM suspension in transient natural convection. In this paper, the implicit finite difference method was used to numerically investigate the transient and steady-state natural convection heat transfer in a square enclosure containing a PCM suspension. The following parameters were included in the simulation:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Natural convection is a situation in which there is no external driving force but the fluid still moves, and the internal force that causes the movement of the fluid is the temperature difference; forced convection is a convection phenomenon that causes the fluid to move when an external force (such as a pump or fan) pushes the fluid. This paper belongs to the natural convection method [12] . The magnitude of heat convection heat transfer follows Newton's cooling equation…”
Section: Mmeat-2022mentioning
confidence: 99%
“…Natural convection is a situation in which there is no external driving force but the fluid still moves, and the internal force that causes the movement of the fluid is the temperature difference; forced convection is a convection phenomenon that causes the fluid to move when an external force (such as a pump or fan) pushes the fluid. This paper belongs to the natural convection method [12] . The magnitude of heat convection heat transfer follows Newton's cooling equation…”
Section: Mmeat-2022mentioning
confidence: 99%
“…Additionally, the magnitude of stream-line circulations is decreased by the ratio of square blockage. Some recent references are seen in [21][22][23][24][25] This article compares the effects of heat transfer between a SiO 2 − water nanofluid and Co ferrofluid inside an enclosure that involves a body that generates heat and has a variety of thermal boundaries. The top wall is insulated; the heated left wall is sinusoidally heated; the right wall is cold; and the bottom wall is uniformly heated.…”
Section: Introductionmentioning
confidence: 99%
“…They found that their modeling results accurately predicted both the improvement and deterioration of natural convection heat transfer. Ho et al [39] used the implicit finite difference method to investigate the transient and steady-state natural convection heat transfer in a square cavity containing a phasechange material (PCM) suspension. They found that the PCM's low latent heat could create oscillatory natural convection under high Rayleigh number.…”
Section: Introductionmentioning
confidence: 99%